(untitled) (Development Service Industry Management, 2025)
The article investigates the essence and strategic role of brand communications in the system of organizational and managerial development of business entities. The relevance of the research is substantiated by the challenges of globalization, digital transformation, increasing competition, and crisis conditions faced by Ukrainian and international companies. Based on the analysis of recent international and domestic scientific publications, the study summarizes current approaches to defining the functions, mechanisms, and strategic importance of brand communications. The author proposes an original interpretation of strategic brand communications as an integrated set of managerial processes that combine both external and internal aspects of enterprise activity, extending beyond the traditional scope of marketing. A three-level mechanism of influence is outlined: the external level (market positioning, reputation, competitiveness), the internal level (corporate culture, HR branding, employee motivation), and the managerial level (integration into strategic planning, support for decision-making, long-term value creation). The study highlights the connection of brand communications with modern management models, such as the Balanced Scorecard, strategic management approaches, and Agile-based models The findings demonstrate that brand communications function as a catalyst for organizational development, supporting innovation, adaptation to crises, and internationalization of business activities. The practical significance of the study lies in the possibility of applying the proposed conceptual framework in the development of strategic communication policies of Ukrainian enterprises under wartime and post-crisis transformations.